The flower of empire an Amazonian water lily, the quest to make it bloom, and the world it created - Holway, Tatiana M. (New York Oxford University Press, 2013)
"In The Flower of Empire, Tatiana Holway tells the story of this magnificent flower, from its discovery to the manner in which its influence touched upon nearly every aspect of Victorian life, art, and culture. Holway recounts how the lily's appearance was reproduced everywhere, giving rise to new experiments in hothouse architecture and eventually serving as a basis for the design of the Crystal Palace, the most impressive demonstration and symbol of the empire's unrivaled industrial might and natural bounty. The Flower of Empire is a revealing and enduring work of cultural history" -- Provided by publisher.
Prologue: Victoria's floras -- Terra incognita -- Perils and wonders -- A floral sensation -- An international tempest -- Return to the wild -- Cultivating Kew Gardens -- His grace and his gardener -- The flowering of Chatsworth -- Golden square -- Evergreens -- Salvaging Kew Gardens -- Trading favors -- Trials and errors -- The great stove -- Reviving Kew Gardens. -- Return to El Dorado -- Paxton, inc -- First bloom -- Nature's engineer -- Empire under glass -- Epilogue: Victoria regia redux.
Includes bibliographical references and index.
Keywords: Victoria amazonica; Botanical gardens -- History -- 19th century. -- England